ANALISIS DAN PEMETAAN KEMISKINAN MULTIDIMENSI PROVINSI SUMATERA BARAT - Yossi Windria (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
This study aims to analyze poverty in West Sumatera Province using multidimensional approach. In multidimensional approach, poverty is measured and analyzed by considering the non-monetary dimension: health dimension, education dimension, and dimension of quality standard of living. The multidimensional poverty measurement in this study used the Alkire-Foster method was introduced by Alkire and Foster (2007) which was later adopted by UNDP to calculate the Multidimensional Poverty Index (MPI) as a permanent feature in the Human Development Report since 2010. Using the Susenas 2016 data, the following results are obtained: (1) The poverty condition is measured taking into account the non-monetary dimension giving a different picture than just taking into account the monetary dimension; (2) Poverty in West Sumatra is a rural phenomenon indicated by the dominance of higher deprived indicators in rural areas; (3) indicators of the use of cooking fuels, pre-school access, and sanitation are the indicators with the highest deprivation (inability of access) in the poor multidimensional population. From a poverty point of view in general, multidimensional poverty is relatively higher than that of monetary poverty. Therefore, multidimensional measurement is needed to complement the measurement of monetary poverty in order to provide a comprehensive picture of poverty estimation.